The Night Of Many Endings - Payne, Melissa (Seattle : Lake Union Publishing, 2021)
"Orphaned at a young age and witness to her brother's decline into addiction, Nora Martinez has every excuse to question the fairness of life. Instead, the openhearted librarian in the small Colorado community of Silver Ridge sees only promise. She holds on to the hope that she'll be reunited with her missing brother and does what she can at the town library. It's her home away from home, but it's also a sanctuary for others who, like her brother, could use a second chance. There's Marlene, an elderly loner who believes that, apart from her husband, there's little good left in the world; Jasmine, a troubled teen; Lewis, a homeless man with lost hope and one last wish; and Vlado, the security guard who loves a good book and, from afar, Nora. As a winter storm buries Silver Ridge, this collection of lonely hearts takes shelter in the library. They'll discover more about each other, and themselves, than they ever knew--and Nora will be forced to question her brother's disappearance in ways she never could have imagined"--Page 4 of cover.
"Bestselling author of The Secrets of Lost Stones"--Cover.
Includes book club questions.
new book 2023 fall.
Keywords: Women librarians -- Fiction; Library users -- Fiction; Orphans -- Fiction; Siblings -- Fiction; Drug addicts -- Fiction; Small cities -- Fiction; Winter storms -- Fiction; FICTION -- Friendship; FICTION -- Family Life -- Siblings; FICTION -- Disaster; Women librarians; Winter storms; Small cities; Orphans; Library users; Drug addicts; Siblings; Colorado -- Fiction; Colorado; Domestic fiction; Novels; Fictional Work; Fiction; Romans